Varroa destructor: how does it harm Apis mellifera honey bees and what can be done about it?. Issue 1 (15th June 2020) - Noël, Amélie; Le Conte, Yves; Mondet, Fanny
Abstract : Since its migration from the Asian honey bee ( Apis cerana ) to the European honey bee ( Apis mellifera ), the ectoparasitic mite Varroa destructor has emerged as a major issue for beekeeping worldwide. Due to a short history of coevolution, the host–parasite relationship between A. mellifera and V. destructor is unbalanced, with honey bees suffering infestation effects at the individual, colony and population levels. Several control solutions have been developed to tackle the colony and production losses due to Varroa, but the burden caused by the mite in combination with other biotic and abiotic factors continues to increase, weakening the beekeeping industry. In this synthetic review, we highlight the main advances made between 2015 and 2020 on V. destructor biology and its impact on the health of the honey bee, A. mellifera . We also describe the main control solutions that are currently available to fight the mite and place a special focus on new methodological developments, which point to integrated pest management strategies for the control of Varroa in honey bee colonies.